Practitioner approaches to measuring community resilience: The analysis of the resilience of communities to disasters toolkit. (November 2020) - Clark-Ginsberg, Aaron; McCaul, Bernard; Bremaud, Isabelle; Cáceres, Gabriela; Mpanje, Desire; Patel, Sonny; Patel, Ronak
Abstract: To be useful for operational programs, measures of resilience must not just be valid, but be easy to use and useful. Unfortunately, while resilience measurement techniques have progressed tremendously over the past decade, most progress has been on improving validity rather than utility and ease of use. In this article we present a new tool for measuring community resilience that incorporates issues of utility and ease of use, the Analysis of Resilience of Communities to Disasters (ARC-D) toolkit. The toolkit was developed over the course of ten years by the international humanitarian and development organization GOAL to enable aid organizations to measure community resilience in a way that supports resilience building interventions. It offers an approach to measurement that is cognizant of the resilience policy landscape, including the Sendai Framework, and approaches to data collection and measurement relevant to aid agencies. We first present the core tenants of community resilience measurement before describing the toolkit, which consists of 30 measures, a guidebook, and an online platform. To illustrate its use, we provide a case study of a resilience building program in Tegucigalpa, Honduras. By developing one of the first resilience toolkits focused beyond validity and providing a description of how such an assessment works, this article has implications for resilience researchers and practitioners.